PARIWISATA RAMAH PENYANDANG DISABILITAS - Zakiyah, Ummi; Husein, Rahmawati (Journal of Governance and Public Policy, 2016)
During this time, the concept of tourism is only designed for people who are normal and has not beendesigned for disabled people. Tourism is right for human being including disabled people. Friendly tourismfor persons with disabilities should provide the facility and accesibility for disabled people. Sen (2007)defines that there are three requirements for disabled people in tourism, those are: availability foraccessibility, transportation, and accomodation.This research is intended to find out what extent tourismmanagement can provide facilityand accesibility for disabled people and what the obstacles and supportingfactors are to develop the friendly tourism for disabled people. This research uses qualitatif method. Tourismplaces proposed in this research are shopping tourism (Malioboro zone), history tourism (Taman Sari andKeraton), and educational tourism (Taman Pintar). Data collected in this research use interview technique,observation, and questioner. This sample of this research has been taken from 100 disabled tourists whotravel to those three objects. The result of this research shows that the facility and accesibility provided todisabled people are still less. Moreover, there is no regulation that obligates the tourism place to servefriendly facility and accesibility for disabled people. Budget resource and human capital are still limited fortourism management to establish friendly tourism place for disabled people. Hence, the research resultrecommends the tourism policy maker to provide friendly facility and accesibility for disabled people.